# Solve for Variable

• May 30th 2009, 11:49 AM
suddenlysmarter
Solve for Variable
S= n/2[2a + (n - 1)d]

please solve and show the steps to get there. I'm confused at how they reached the answer the book has. Thanks
• May 30th 2009, 01:24 PM
pberardi
Quote:

Originally Posted by suddenlysmarter
S= n/2[2a + (n - 1)d]

please solve and show the steps to get there. I'm confused at how they reached the answer the book has. Thanks

For which variable do you need to solve for?
• May 30th 2009, 02:57 PM
mr fantastic
Quote:

Originally Posted by suddenlysmarter
S= n/2[2a + (n - 1)d]

please solve and show the steps to get there. I'm confused at how they reached the answer the book has. Thanks

This is the formula for the sum of the first n terms of an arithmetic series. I suggest you consult your textbook or class notes for the derivation (or Google it).

If you're attempting to apply this formula in a specific question, it would help if you actually posted that question. We are not mind readers.
• May 30th 2009, 05:50 PM
suddenlysmarter
Sorry it was solve for a
Sorry it was solve for a and I just can't see to figure out how they achieved the answer they got. How would you approach this. In order for me to understand I would need to see how you reached your answer.

Anyone who is up for the challenge. I would greatly appreciate it.
• May 30th 2009, 05:57 PM
wytiaz
S = n/2[2a + (n - 1)d]

2S/n = 2a + nd - d

2S/n - nd + d = 2a

S/n - (1/2)nd + (1/2)d = a
• May 30th 2009, 05:59 PM
wytiaz
S= n/2[2a + (n - 1)d]

2S/n = 2a + nd - d

2S/n - nd + d = 2a

S/n - (1/2)nd + (1/2)d = a
• May 30th 2009, 06:01 PM
pberardi
Quote:

Originally Posted by suddenlysmarter
Sorry it was solve for a and I just can't see to figure out how they achieved the answer they got. How would you approach this. In order for me to understand I would need to see how you reached your answer.

Anyone who is up for the challenge. I would greatly appreciate it.

S = n/2[2a+(n-1)d] Solve for a
First multiply by 2
2S = n[2a +(n-1)d]
Divide by n
2S/n = 2a + (n-1)d
Subtract the term (n-1)d
2S/n -(n-1)d = 2a
Divide by 2
S/n -(n-1)d/2 = a

Simplify as you wish. Helps?